2007 IEEE International Conference on Control and Automation 2007
DOI: 10.1109/icca.2007.4376671
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed Nitrogen Status Estimation of Vis-NIR Spectra Based on Partial Least Square and BP Neural Network

Abstract: A combined estimation model, artificial neural network (ANN) combined with partial least square regression (PLS) method, has been developed for estimation of rapeseed N status. Spectra tests were performed on the rapeseed canopy of 150 samples in the field using a spectrophotometer (325-1075nm). 5 optimal PLS principal components were determined by PLS analysis with cross-validation. They were selected as the input of BP neural network to establish the prediction model. The node number of input layer, hidden l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Some reports are available on use of visible and near infrared (VIS/NIR) spectroscopy for identification of cultivar [5,6]. Study of rapeseed using visible and infrared spectroscopy has been reported [7,8,9,10]. However, these papers are just related to physical and chemical analysis, such as oil content, sinapic acid esters assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports are available on use of visible and near infrared (VIS/NIR) spectroscopy for identification of cultivar [5,6]. Study of rapeseed using visible and infrared spectroscopy has been reported [7,8,9,10]. However, these papers are just related to physical and chemical analysis, such as oil content, sinapic acid esters assessment.…”
Section: Introductionmentioning
confidence: 99%